Development of Speech Skills of A Younger Student (Eurasian Scientific Herald, 2023)
The article examines the features of the speech development of younger students. The functions of speech are determined and recommendations are given for the development of speech of younger schoolchildren during school hours and after school hours. Mastering speech is a necessary condition for the formation of a socially active personality. Primary school, according to the author, should pay great attention to this. Extracurricular activities can greatly help children develop their speech.